Proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction 2014
DOI: 10.1145/2559636.2559656
|View full text |Cite
|
Sign up to set email alerts
|

Meet me where i'm gazing

Abstract: In this paper we provide empirical evidence that using humanlike gaze cues during human-robot handovers can improve the timing and perceived quality of the handover event. Handovers serve as the foundation of many human-robot tasks. Fluent, legible handover interactions require appropriate nonverbal cues to signal handover intent, location and timing. Inspired by observations of human-human handovers, we implemented gaze behaviors on a PR2 humanoid robot. The robot handed over water bottles to a total of 102 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(53 citation statements)
references
References 37 publications
(47 reference statements)
4
49
0
Order By: Relevance
“…Results from this study indicate that when the robot continually displays face gaze during the handover, participants reach for the object even earlier than when only the shared attention gaze is displayed. In addition, this study reaffirmed the finding from the first robot-to-human handover study [34] that participants prefer conditions with face gaze over conditions without it.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Results from this study indicate that when the robot continually displays face gaze during the handover, participants reach for the object even earlier than when only the shared attention gaze is displayed. In addition, this study reaffirmed the finding from the first robot-to-human handover study [34] that participants prefer conditions with face gaze over conditions without it.…”
Section: Introductionsupporting
confidence: 82%
“…In our earlier work [34] we demonstrated that when the robot gazes at the handover position (a location where the handover is projected to happen) continually during the handover (shared attention gaze), participants reach for the offered object significantly earlier than when this gaze cue is absent during the interaction. However, if the robot displays a variation of this gaze cue, i.e.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yamazaki et al [35] also demonstrated the importance of gaze timing in turn-taking interactions. Also, in a handover setting where the robot handed bottles to human subjects, [25] empirical evidence reveals that gaze cues can improve hand over timing and the subjective evaluation of the robot.…”
Section: Related Workmentioning
confidence: 99%